Molybdenum(VI) complexes with ligands derived from 5-(2-pyridyl)-2H-tetrazole as catalysts for the epoxidation of olefins - Nunes, Martinique S. (2023)
The development of effective catalytic epoxidation processes that are an alternative to stoichiometric non-selective oxidation routes is important to meet environmental sustainability goals. In this work, molybdenum (VI) compounds bearing 5-(2-pyridyl)-2H-tetrazole derivatives as organic components, namely the ionic and neutral mononuclear complexes (H2ptz)[MoO2Cl2(ptz)] (1) and [MoO2Cl2(tBu-ptz)] (2), and the new Lindqvist-type polyoxometalate (POM) [tBu-Hptz]2[Mo6O19] (3), where Hptz = 5-(2-pyridyl)tetrazole and tBu-ptz = 2-tert- butyl-5-(2-pyridyl)- 2H-tetrazole, were studied as epoxidation catalysts using readily available and relatively ecofriendly hydroperoxide oxidants, namely hydrogen peroxide and tert-butyl hydroperoxide (TBHP). The pre-pared catalysts were very active. For example, 100% cis-cyclooctene conversion and 100% epoxide selectivity were reached at 1 h for 1 and 3, and 10 min for 2 (with TBHP). Catalytic and characterization studies indicated that the mononuclear complexes suffered chemical transformations under the reaction conditions, whereas 3 was structurally stable. This POM acted as a homogeneous catalyst and could be recycled by employing an ionic liquid solvent. The POM can be synthesized from 2 under different conditions, including those used in the catalytic process. Moreover, 3 was an effective epoxidation catalyst for a biobased substrate scope that included fatty acid methyl esters and the terpene dl-limonene.